SAT0314 Impact of Urate-Lowering Therapy in the Risk of Acute Inflammation Episodes During Hospital Admissions in Patients with Gout. (9th June 2015) - Perez-Ruiz, F.; Chinchilla, S.P.; Urionagüena, I.
Abstract : Background: An increased risk (OR 4.1, 95% CI 1.8-9.2) of acute inflammation episodes during hospital admission in patients with gout, has been reported in an online survey (1). Less than half of the patients were on urate lowering therapy (ULT); in those treated the levels of uricaemia and adequacy of the treatment are unknown. The authors' advice was to administer preventive treatment during admissions. Objectives: To evaluate the time-associated impact of ULT, in gout patients with and without hospital admissions. Methods: Case-control study within a nested cohort of patients with prospective follow-up, during 6 months (June-December 2014). The appearance of at least one inflammation episode during admission was analyzed. The ratio of inflammation episodes in patients with and without hospital admissions was compared; as well as treatment, basal data prior to treatment and during follow-ups, and uricaemia prior to the inflammation episode during admission. Results: 274 patients, all of them with ULT (91.6% men, age 61±13 years, basal serum urate levels 9.1±1.4 mg/dL, time of disease evolution 7.7±8.1 years, 37% with tophi, 40% with poliarticular distribution). Twenty-eight patients (10.2%, 20.4/100 patient/years) had an admission and ten an episode of arthritis: 2 of them due to calcium pyrophosphate, 8 due to monosodium urate. The admitted patients were elder, compared to the not admitted (67.0±10 vs 61±13, p=0.03), but showed similarity in the rest of the data. Amongst the admitted patients, no statistically significant differences were observed between those with gout and those asymptomatic, regarding age (71±7 vs 64±10), serum urate basal levels (9.0±1.1 vs 9.2±1.0), or previous to the episode (5.2±1.7 vs 5.1±1.1), the rate of uricaemia in therapeutic level <6mg/dL (75% vs 89%, p=0.32), presence of tophi, poliarticular distribution or episodes during the year prior to treatment.The analysis per year of follow-up showed that 7/8 episodes were observed during the first two years and no episodes after 3 or more years of treatment (rates, ORs & CI limits are shown in the table ). Conclusions: There is a clear tendency for risk reduction of acute inflammation episodes during hospital admission, in patients treated with ULT who have an acceptable uricaemia control and within therapeutic levels. The risk of suffering an acute inflammation episode is similar to that previously reported; nonetheless, the risk is striking only during the first year of treatment, plausible during the second, but not observed afterwards. References: Dubreuil M, et al. Am J Med 2013;126:1138-1141. Disclosure of Interest: F. Perez-Ruiz Consultant for: AstraZeneca, Menarini, Pfizer, Speakers bureau: AstraZeneca, Menarini, S. Chinchilla: None declared, I. Urionagüena: None declared